CIREFCA: The promises and reality of the International Conference on Central American Refugees, an independent report - Aguilar Zinser, Adolfo (Centre for Immigration Policy and Refugee Asistance, 1991)
El documento en un análisis de los refugios en América Central, las políticas, financiamiento, a organizaciones gubernamentales y no gubernamentales.